2019
DOI: 10.31080/aspe.2019.02.0159
|View full text |Cite
|
Sign up to set email alerts
|

Experience in the Treatment of Choledochal Cyst with Robot-Assisted Surgery in Children: and "The Current State of Minimally Invasive Surgery in this Anomaly”

Abstract: Report our experience in the treatment of choledochal cyst with robot-assisted surgery in children and perform a current analysis of both approaches of minimally invasive surgery, for this anomaly. Results:We treated 4 patients with choledochal cyst, relation 1:3 female, the averages was in age 3 years, weight 15 kg and height 94.2 cm. Type 1-A cysts were three and one 1-C, the average size of the cysts, 9.6 cm. Clinically, they presented: abdominal mass 3, jaundice episode 3 and fever 2. The following are ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…Hepatopancreatobiliary RAS in children inevitably involves high complexity, such as Kasai portoenterostomies and choledochal cyst resection [108][109]. Furthermore, liver resection, robot-assisted generally indicated for treatment of tumors [110].…”
Section: General Surgery (Gastrointestinal and Hepatopancreatobiliary)mentioning
confidence: 99%
See 3 more Smart Citations
“…Hepatopancreatobiliary RAS in children inevitably involves high complexity, such as Kasai portoenterostomies and choledochal cyst resection [108][109]. Furthermore, liver resection, robot-assisted generally indicated for treatment of tumors [110].…”
Section: General Surgery (Gastrointestinal and Hepatopancreatobiliary)mentioning
confidence: 99%
“…In 2006, the first pediatric RAS choledochal cyst resection was reported [116]. Since that time and up to 2019, several authors have reported cohorts of 1 to 39 pediatric patients undergoing RAS choledochal cyst resection [109]. A recent publication informed 70 cases with RAS and 70 cases by conventional laparoscopy, and concluded that RAS choledochal cyst excision and hepaticojejunostomy were associated with better short-term intraoperative and postoperative outcomes, and proved the safety and feasibility of RAS in children with choledochal cysts [117].…”
Section: Choledochal Cyst Resectionmentioning
confidence: 99%
See 2 more Smart Citations
“…This also happened to Meehan and Sandler [27] . Robotic assistance is ideal for complex hepatobiliary cases and thoracic surgery, particularly for solid mass resection [35,36] .…”
Section: Patients Between 3 and 5 Kg With Rats Are A Great Challenge mentioning
confidence: 99%